PESTICIDLER HÁM OLARDÍŃ AQÍBETLERI HAQQÍNDA - Qosnazarov, K.A.; Temirbekov, O.; Ermakova, I.R. (ILIM hám JÁMIYET, 2021)
The article discusses anthropogen factors which impact on nature of Aral Sea territory and environment. Therefore the mentioned factors rapidly changes enviroument and create catastrophic situations. These changes are not just ecological problem of Aral Sea territory it is also the ecological problem of all people of the world.